PENINGKATAN KUALITAS BERMAIN DALAM CABANG OLAHRAGA FUTSAL - Ariel Limbong; Azi Faiz Ridlo; Tatang Iskandar (Universitas Islam 45 Bekasi, 2022)
The purpose of this paper is to educate teenagers around Malacca 4 about the latest regulations and also provide education about how to play well in futsal. This paper is the result of KKN activities that have been carried out with a program to improve the quality of sports games. The background of this problem is the lack of education or understanding of teenagers around Malacca 4 about the rules and how to play well in futsal. The Community Service Program implemented here contains three activities, namely; (1) Webinar